2018
DOI: 10.1016/j.envres.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tungsten and incident cardiovascular disease in the Strong Heart Study: An interaction with urinary molybdenum

Abstract: The association between W and CVD incidence and mortality was positive although non-significant at lower urinary Mo levels and significant and inverse at higher urinary Mo levels. Although prior cross-sectional epidemiologic studies in the general US population found positive associations between urinary tungsten and prevalent cardiovascular disease, our prospective analysis in the Strong Heart Study indicates this association may be modified by molybdenum exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“… 86 Moreover, urinary cadmium was associated with increased risk of ischemic stroke but had a more pronounced association in participants in the lowest tertile of serum Zn levels. 86 The few studies conducted to date have had the power to study effect modification between essential trace metals and toxic metals in reducing CVD risk.…”
Section: Epidemiological Studies Linking Metal Exposures To Cvd Riskmentioning
confidence: 96%
See 1 more Smart Citation
“… 86 Moreover, urinary cadmium was associated with increased risk of ischemic stroke but had a more pronounced association in participants in the lowest tertile of serum Zn levels. 86 The few studies conducted to date have had the power to study effect modification between essential trace metals and toxic metals in reducing CVD risk.…”
Section: Epidemiological Studies Linking Metal Exposures To Cvd Riskmentioning
confidence: 96%
“…The available studies have also reported a significant association between imbalances in essential metals and CVD risk. Specifically, imbalanced levels of Zn, 20 , 21 Cu, 22–26 Cr, 27 , 28 Co, 29 , 30 Mg, 22 , 24 , 31–69 Se, 61 , 70–84 Ni, 85 and W 86–89 were associated with an increased CVD risk. Other studies, however, failed to establish a significant association between these essential metals and CVD risk 22 , 44 , 58 , 61 , 65 , 85 , 88 , 90–94 …”
Section: Epidemiological Studies Linking Metal Exposures To Cvd Riskmentioning
confidence: 99%
“…Secondary analyses were performed to explore whether the associations between arsenic exposure and the continuous measures of LV geometry and functioning were modified by sex, smoking status, BMI (<30, ≥30 kg/m 2 ), lipid treatment (no, yes), fasting glucose (normal, impaired), and BP (normal, prehypertension, or hypertension) by including interaction terms in linear regression models. In sensitivity analyses, we also further adjusted for tungsten and uranium, metals that tend to cooccur with arsenic in drinking water 31 and could be related to cardiovascular disease, 43,44 with similar findings (not shown). The data were analyzed using R software (version 3.0.3; R Development Core Team 2014).…”
Section: Methodsmentioning
confidence: 73%
“…More studies are required on other microminerals since they have been less considered and results remain controversial. Serum molybdenum levels have been associated with T2DM [137], whereas the relationship between tungsten and CVD incidence has proved to be molybdenum-dependent, which underlines the promising role of molybdenum exposure in the disease [138]. Selenium and iodine may be implicated in DM, although results of epidemiologic studies and animal experiments are unclear [139].…”
Section: Micronutrients 221 Micromineralsmentioning
confidence: 99%